ABILITY LEVEL TO DEVELOP A CASE STUDY RESEARCH PLAN OF SIXTH GRADE ENGLISH DEPARTMENT STUDENTS OF STKIP PGRI PACITAN IN THE ACADEMIC YEAR 2014-2015 - Kurniawan, Agung Budi (Jurnal Humaniora, 2015)
Case study is one of most used research type in language area especially in English education area. This research is actually a normal situation of classroom lecture of Language Teaching Learning Research subject. The subject of this research is all students of sixth semester of English department of STKIP PGRI Pacitan in the academic year 2014-2015. They consist of 2 classes which contain 65 students. Itâs existed two meetings in LTLR subject. The first is the fourth meeting. Researcher taught all theories, concept, and frame work of case study. The second meeting is the fifth meeting of LTLR subject. It was conducted by giving task of developing a case study research plan to students. Researcher gives 4 choices of themes of case study according to kinds of case study which is education, evaluative, ethnography, and multi-side case study. Every student must choose one of them and not allowed to change the topic or title. Then, they have to develop the theme and topic to a case study frame work which consists of theme of case study, identification of the problem, objectives, object of the research, technique of data collection, instrument of the research, and research procedure. Every part has scoring and qualification criteria. In the end of every work, all scorings are collected of which maximum score is 100. Overall, sixth semester studentsâ ability to develop case study research plan of English department of STKIP PGRI Pacitan in the academic year 2014-2105 is average.Key words: developing, case study, research, plan, sixth grade, English department, STKIP PGRI Pacitan 2014 -2015